Contextualizing Basic Hospitality Learning through Ethno-Project-Based Teaching Module to Enhance Critical Thinking Skills of Vocational High School Students - Diarini, I Gusti Ayu Agung Sinta; Sentosa, I Putu Pranatha; Widyastuti, Ni Kadek (Universitas Pendidikan Ganesha, 2025)
The limited availability of meaningful teaching modules poses a challenge in vocational hospitality education, especially in the implementation of the Merdeka Curriculum, which demands the reinforcement of students’ critical thinking skills. This situation impacts the development of essential competencies required to address real-world workplace problems. This study aims to develop, validate, and evaluate the practicality and effectiveness of an Ethno Project-Based Teaching Module to enhance students’ critical thinking skills in the Fundamentals of Hospitality subject. This research employed a Research and Development (R&D) design using the ADDIE model. The subjects involved 64 vocational students divided into experimental and control groups. Data were collected through validation questionnaires, practicality questionnaires, and critical thinking skill tests. The data were analyzed using a t-test and n-gain score calculation. The results indicated that the module achieved a “Very Good” qualification from content experts (average score of 4.89) and “Good” to “Very Good” from language experts (average score of 4.15). The module’s practicality was rated “Very Good” by both students (average 3.29) and teachers (average 3.44). Furthermore, the module was proven effective in improving students’ critical thinking skills, as reflected in an average n-gain of 0.52 (moderate) for the experimental group and 0.22 (low) for the control group, with a t-test value of 13.698 and a significance level of 0.000 (< 0.05). These findings suggest that the Ethno Project-Based Teaching Module is feasible to be implemented for optimizing critical thinking skills in vocational education.